PENERAPAN REGRESI KUANTIL DALAM MENGANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM - Christa Hardiyanti; Edi Subiyantoro; Nanik Sisharini; Fransiskus Xaverius Agung Perkasa Jampur (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This research using quantile regression analysis is to test how many investors and consumer goods companies are interested in still referring to financial ratios, namely the ratio of liquidity, activity, profitability and leverage to stock returns. The samples used were taken from 45 consumer goods companies listed on the Indonesia Stock Exchange in the 2018-2020 period. Hypothesis testing uses a quantile regression analysis technique which will be divided into three groups. The results of the analysis show that in the quintile group of one investor 11.3% are interested in investing due to the profitability and leverage factors of the company. The results of the analysis show that the net profit margin (NPM) and debt to equity ratio (DER) have a significant effect on stock returns. The second quantile group of investors' interest in companies is 42% due to the liquidity factor. The results ofanalysis results show that the cash ratio has a significant effect on stock returns; in quantile groups, there is 384% of investors' interest in companies. From the current ratio, cash ratio, TATO, FATO, ROE, NPM , DAR and DER h,ave o effect on stock returns.